Water resistant reactive microcapsules for self-healing coatings in harsh environments. (17th May 2016) - Sun, Dawei; Zhang, He; Tang, Xiu-Zhi; Yang, Jinglei
Abstract: Double-shelled microcapsules containing liquid 4, 4′-bis-methylene cyclohexane diisocyanate (HMDI) with outstanding water resistance are successfully synthesized via combination of interfacial and in-situ polymerization reactions in an oil-in-water emulsion. The diameter and shell thickness of microcapsules increased under lower agitation rate. The relative residue of core content of microcapsules remains more than 90% after 24 days in both ambient open air and water. Manually scratched polymer coatings with both fresh and conditioned microcapsules showed satisfactory anticorrosion performance in salt water via self-healing functionality. In addition, self-healing coatings with fresh microcapsules after immersion in ambient water for 30 days still possessed superior anticorrosion performance. Graphical abstract: Highlights: Double-shelled microcapsules were synthesized via shortened in-situ polymerization. Resultant capsules showed excellent survivability in various aqueous solutions. Fresh/Treated capsules in coating can self heal scratch after soaking in salt water.